The qualitative study of career sustainability of creative studies graduates (Gen Z) in Malaysia - Yasin, M Al-imran; Mohd Nawi, Muhammad Alif Hakimi (Human Resource Management Academic Research Society, 2024)
The creative industry is known as an industry that benefits young generations and would provide a working ecosystem where the gig economy would dominate the work nature. Gig economy by nature is known for its temporary and flexible working environment that would attract younger generations to commit to it while and to make the situation worse is the influx of the Millennials generation that might not be employed due to the downturn of the economy especially in the aftermath of COVID-19. This study is a qualitative method of research that would conduct two (2) focus group discussions (FGD) with 2 different sets of generation which is the Millennials and generation Z with three (3) people per each session from the ranges of age of 21-40 years old. The objective of this study is to understand what would be the career sustainability of the students and graduates of creative studies once they enter the workforce. This study is expected to provide insights to the researchers that are mainly educators of what can be done to improvise the existing practice in the creative study ecosystem.